Breast cancer prevention through the SADARI program in Padang Mutung Village, Kampar Regency - Melly Melly; Magdalena Magdalena; Kustiasih Lestari (Universitas Muhammadiyah Magelang, 2022)
One of the main causes of death in the globe is cancer. This number is predicted to rise to 26 million by 2030, with 17 million of them expected to pass away. The purpose of this community service is to increase the knowledge and ability of PKK cadres in an effort to prevent breast cancer by conducting SADARI examinations in Mutung Village, Kampar Regency. The method of implementing this programconsists of the preparation stage, the implementation stage through training and practice of breast examination, and evaluation of the knowledge and skills of PKK cadres. This program succeeded in forming a cadre of breast cancer care. Participants' knowledge and skills have improved as a result, with an average post-test score of 90% and 93.3%, respectively. After this program, it is intended that the cadres would be able to educate the public, particularly mothers and teenagers, about breast cancer early detection.